2017
DOI: 10.1063/1.4991608
|View full text |Cite
|
Sign up to set email alerts
|

DFT modeling of carbon incorporation in GaN(0001) and GaN(0001¯) metalorganic vapor phase epitaxy

Abstract: The carbon incorporation mechanism in GaN(0001) and GaN(0001¯) during MOVPE was investigated using density functional theory (DFT) calculations. The results confirm that the crucial factors for carbon incorporation are Fermi level pinning and accompanying surface band bending. In addition, the lattice symmetry has a strong dependence on the stability of carbon in a few subsurface layers, which results from interactions between the impurities and surface states. It was shown that these effects are responsible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…There are some theoretical studies on surface states of nitride surfaces and also a recent paper on the impact of the surface structure on carbon incorporation. [18][19][20] However, the latter study is limited to potential incorporation sites for a single C atom. In this work, thick GaN layers were grown by HVPE and intentionally doped with carbon with the objective to identify the occupation site of carbon or its complexes experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…There are some theoretical studies on surface states of nitride surfaces and also a recent paper on the impact of the surface structure on carbon incorporation. [18][19][20] However, the latter study is limited to potential incorporation sites for a single C atom. In this work, thick GaN layers were grown by HVPE and intentionally doped with carbon with the objective to identify the occupation site of carbon or its complexes experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…From the SEAQT analysis, a non-equilibrium state evolution of the adsorption process was obtained, and the adsorption probability was found to be 7.06 × 10 −3 in (0001) and 3.32 × 10 −6 in (000−1) at 1000 °C. A C impurity incorporation model was proposed here in which it was assumed that the C impurity concentration was proportional to the CH 4 adsorption probability and to the Boltzmann factor calculated from the energy of the C impurity at the first surface layer [51]. As a result of this model, the ratio of the C impurity concentration in (0001) to that in (000−1), cC(0001)/cC(0001), was 1.25×101.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Kempisty et al reported the depth profiles of the C impurity energy in (0001) and (000−1), i.e., the comparison of the total energies of two-surface slab models, where the one nitrogen atom at the selected layer near the surface (i.e., the 1st, 2nd, …, 8th, or 10th atomic layers from the surface) is substituted by a carbon atom [49]. Figure 7 shows the result of Reference [51] for 3Ga-H and 3N-H surfaces and the Boltzmann factors, exp(E/kBT), at 1000 °C calculated from these energies. As can be seen, the C atoms at the fourth layer onwards from the surface were almost in the same situation as those in the bulk (i.e., layers deep enough).…”
Section: Impurity Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable research on the reduction of impurities in polar plane growth, such as þc(0001)and Àc(000À1)-plane growth, has been reported due to wide practical uses of the resulting materials. [6][7][8][9] Conversely, there have been few reports on impurity incorporation in the case of nonpolar plane growth, such as m(10À10)-plane growth, although layers grown without a polarization field along the growth direction are advantageous for device performances. [10] In 2018, Tanaka et al [11] reported that the oxygen concentration in GaN films grown on 5 off m-GaN toward the Àc-direction (Àc 5 off ) by metal-organic vapor phase epitaxy (MOVPE) was below that on 5 off m-GaN toward the þc-direction (þc 5 off ).…”
mentioning
confidence: 99%